THE UNCERTAIN DECORUM OF ONLINE IDENTIFICATION: A STUDY IN QUALITATIVE INTERVIEWS - DiBella, Samuel (AoIR Selected Papers of Internet Research, 2020)
This study explores the ethics and motivations of online identification—how and why people collect and publish identifying information about others online. In seven interviews, activists, Internet users, advocates, and journalists were asked about their investigative practice and how they viewed the ethics of deanonymization. Using ethnographic interviewing techniques and a thematic analysis inspired by grounded theory, I describe respondents’ investigations and compare them to existing theories in surveillance studies, online anonymity, and digital vigilantism. Respondents often struggled with making their work accessible and impactful in an ethical manner. They obfuscated irrelevant information that might incite online harassment and took care in who they collaborated with. The respondents also debated what to do when people misinterpreted their work or thought that they had acted unjustly. The precautions they incorporated into their publications are examples of how people navigate online ethics when there isn’t a clear standard for moral decisions. Ultimately, the interview results did not follow models of digital vigilantism and doxxing, and I caution against using those terms to apply to cases like those described in this study. I also make suggestions for how these results could augment theoretical models of anonymity, particularly how respondents’ investigative techniques and backgrounds lead them to different moral commitments.